Effects of Flipped Classroom Strategy and Laboratory Methods on Students’ Attitude Towards Physics in Abak Education Zone of Akwa Ibom State, Nigeria - MFON, Frank Charity; AGOMMUOH, Patience Chinyere; ALPHONSUS, Umoren Friday (Ilorin Journal of Education, 2025)
This study explored the impact of flipped classroom and laboratory teaching methods on secondary school students’ attitudes toward Physics in the Abak Education Zone of Akwa Ibom State, Nigeria. A quasi-experimental design with pre-test and post-test assessments was used across three groups: the Flipped Classroom Method (FCM), the Laboratory Teaching Method (LTM), and a control group taught with the traditional Lecture Method (LM). From a population of 13,730 Senior Secondary Two (SS2) students in 63 public schools, a purposive sample of 168 students from three schools was selected. The research instrument, the Physics Students’ Attitudinal Scale (PSAS), was validated by experts and demonstrated a reliability coefficient of 0.80 using the Kuder-Richardson 20 (KR-20) method. Data were analyzed using mean, standard deviation, and ANCOVA. Findings revealed that students exposed to the flipped classroom method achieved significantly higher mean attitude scores than those in the other groups. Although male students had slightly higher gains, there was no statistically significant gender difference across the teaching methods. The study concluded that the flipped classroom approach effectively improves students’ attitudes toward Physics regardless of gender and recommended its adoption in public schools, along with the provision of adequate resources for successful implementation.